‘Cili Solok’ : Is it possible to market outside Kelantan? - Wan Zaiti Hastuti Wan Zahari (2015)
Tutie’s chilli has bought a piece of land which is 750 square meters and another lot is rented on an yearly basis. The owner has cultivated “Cili Solok” for about 1500 plants and also owns 22 greenhouses equipped with fertigation system. There are so many challenges in vegetable industry such as the country’s productions still do not meet the country’s demand, small-scale cultivation and high production costs. Local farmers also have to compete with other vegetable’s producers which offer low-cost, such as Thailand and China. Malaysian vegetable industry transformation is heading towards a competitive industry and sustainable development.